Clinical and radiological results of cemented proximal femoral nails (Annals of Medical Research, 2022)
Aim: Osteoporotic interthoracanteric fractures are an important health problem affecting the elderly population. Cement augmentation is a modification that has been applied with increasing frequency in recent years. In our study, we aimed to retrospectively analyze the clinical and functional results of proximal femoral nails (PFN) with cemented augmentation.Materials and Methods: Sixty-five patients who met the inclusion criteria were included in the study. PN1 PFNA Nail - Tasarım Medikal ® - İstanbul nails were applied to all patients. Information such as spreading area of cement, closest distance of cement to cartilage, number of additional fluoroscopy for cementing procedure, amount of cement were collected. Reductions were evaluated according to the Modified Baumgaertner Criteria and rehabilitation protocols were applied. Pain of the patients was evaluated with the vas score, and hip functionality with the Harris score. Patients with a minimum follow-up of 2 years were included in the study.Results: The amount of cement placed in the femoral heads of 37 patients with Singh index values of 1 and 2 was found to be 2.9±0.5 ml, significantly higher than the amount of cement placed in the femoral head (2.1±0.3 ml) of patients with Singh index 3, 4, 5 (p
Keywords: hip; fracture; cement; augmentation